1994
DOI: 10.1002/jbmr.5650091011
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin inhibits testosterone and luteinizing hormone secretion through a mechanism involving an increase in camp production in rats

Abstract: Effects of calcitonin peptides, including human calcitonin (hCT), salmon calcitonin (sCT), and calcitonin gene-related peptide (CGRP), on the secretion of testosterone and luteinizing hormone (LH) in male rats were studied. Male rats were injected intravenously with human chorionic gonadotropin (hCG), calcitonin peptides, or hCG plus calcitonin peptides. Blood samples were collected at several intervals following hormone challenge. In an in vitro experiment, testis blocks were incubated with hCG (0, 0.05, 0.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Male Sprague-Dawley rats weighing 300-350 g were housed in a temperature controlled room (22 AE 18C) with 14 h of artificial illumination daily (06:00-20:00 h) and given food and water ad libitum. Male rats, which were divided into 8 teams with 6-7 rats in each, were catheterized via the right jugular vein [Wang et al, 1994]. Twenty hours later, they were injected with saline (1 ml/kg) as vehicle, CCN (1 mg/ml/kg), EC (1 mg/ml/kg), EGCG (1 mg/ml/kg), human chorionic gonadotropin (hCG, 5 IU/ml/kg), hCG þ CCN, hCG þ EC, and hCG þ EGCG via the jugular catheter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male Sprague-Dawley rats weighing 300-350 g were housed in a temperature controlled room (22 AE 18C) with 14 h of artificial illumination daily (06:00-20:00 h) and given food and water ad libitum. Male rats, which were divided into 8 teams with 6-7 rats in each, were catheterized via the right jugular vein [Wang et al, 1994]. Twenty hours later, they were injected with saline (1 ml/kg) as vehicle, CCN (1 mg/ml/kg), EC (1 mg/ml/kg), EGCG (1 mg/ml/kg), human chorionic gonadotropin (hCG, 5 IU/ml/kg), hCG þ CCN, hCG þ EC, and hCG þ EGCG via the jugular catheter.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma was separated by centrifugation at 8,000g for 3 min. The concentration of testosterone in each plasma sample was measured by radioimmunoassay (RIA) [Wang et al, 1994].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, suggest that signal for sCT-stimulated E 2 release might be transduced through cAMP pathway and interaction between sCT and hCG on the signal transduction in fish ovary is still open to elucidate. Increased production of cAMP caused by CT has been demonstrated in perfused rat bone, osteoblast like cell line, osteoclast, atria and aortic smooth muscle (Kubota et al, 1985;Sugimoto et al, 1986;Nicholson et al, 1987;Wang and Fiscus 1989;Iida-Klein 1992), and in rat testicular and anterior pituitary gland (Wang et al, 1994) substantiate the action of CT through cAMP path way in fish ovarian follicles. Our present finding on the stimulatory role of sCT on basal and hCG-induced E 2 production by fish ovarian follicles is completely opposite to the observed action of CT in mammalian ovary and testes in the regulation of steroid production.…”
Section: Discussionmentioning
confidence: 80%
“…Specific CT-binding sites have been found in brain and pituitary gland (Maurer et al, 1983) and in ovary and testis in mammal (Chausmer et al, 1982). Wang et al, (1994) found that www.intechopen.com CT-like peptides, human CT, salmon CT and CT-gene related peptide inhibit spontaneous and gonadotropin-stimulated testosterone secretion by acing directly on testes and also by reducing the release of pituitary luteinizing hormone (LH). Inhibition of salmon CT on secretion of progesterone-and gonadatropin-releasing hormone (GnRH)-stimulated release of pituitary LH in rat also has been documented (Tsai et al, 1999).…”
Section: Other Function Of Ct In Vertebratesmentioning
confidence: 99%